2020
DOI: 10.3390/molecules25214947
|View full text |Cite
|
Sign up to set email alerts
|

Development of HPLC Method for Quantification of Sinigrin from Raphanus sativus Roots and Evaluation of Its Anticancer Potential

Abstract: Sinigrin, a precursor of allyl isothiocyanate, present in the Raphanus sativus exhibits diverse biological activities, and has an immense role against cancer proliferation. Therefore, the objective of this study was to quantify the sinigrin in the R. sativus roots using developed and validated RP-HPLC method and further evaluated its’ anticancer activity. To achieve the objective, the roots of R. sativus were lyophilized to obtain a stable powder, which were extracted and passed through an ion-exchange column … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…WC was shown to contain sinigrin (2-propenyl glucosinolate) (65), which is a precursor of allyl isothiocyanate. This compound has diverse biological activities (66), including anticancer, anti-inflammatory, antibacterial, antifungal, antioxidant, and wound healing effects (67). In line with this study, the presence of sinigrin in WCE was previously reported by Dighe and Charegaonkar (68) and Amir et al (69).…”
Section: Discussionsupporting
confidence: 84%
“…WC was shown to contain sinigrin (2-propenyl glucosinolate) (65), which is a precursor of allyl isothiocyanate. This compound has diverse biological activities (66), including anticancer, anti-inflammatory, antibacterial, antifungal, antioxidant, and wound healing effects (67). In line with this study, the presence of sinigrin in WCE was previously reported by Dighe and Charegaonkar (68) and Amir et al (69).…”
Section: Discussionsupporting
confidence: 84%
“…Among the compounds identified in red kale subjected to prior in vitro digestion, sinigrin and spirostanol type saponins, usambaresine and hesperitin are known for their biological activity. Sinigrin is a compound that belongs to the glucosinolates, present in various plants of the Brassicaceae family, with well-documented anticancer activity [15,[21][22][23][24][25][26]. Studies have shown its effect on changes in gene expression in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, by preventing the activation of the NLRP3 inflammasome or the NF-B/MAPK pathways in macrophages, sinigrin reduces the generation of inflammatory mediators [23]. Sinigrin also induce overexpression of caspase-3 in DU-145 s cells and increase apoptosis [24].…”
Section: Discussionmentioning
confidence: 99%